Strategi Penetapan Harga Jual Pada Komunitas Dropshiper Di Lingkungan Universitas Islam Madura - Sakdiyah, Halimatus; Wardaturrohah, Wardaturrohah (Unversitas Islam Madura, 2021)
The purpose of this study was to determine the selling price setting strategy used by the dropshiper community in the Islamic University of Madura. The type of research method used is descriptive quantitative. Sources of data in this study are primary data and secondary data. With data collection methods, namely interviews, observation, documentation and literature study. The results showed that the strategy of fixing the selling price in the drosphiper community in the Islamic University of Madura used two strategies: first, the standard cost-based pricing strategy was determined by adding a certain percentage of costs to all items in a product class. second, using a demand-based selling price strategy. This skiming pricing strategy is determined by setting a high price for a new or innovative product during the introductory stage, then lowering the price when the competition is getting tighter. Keywords: selling price determination strategy, dropshiper